Effect of calcium carbonate on the mechanical and thermal properties of isotactic polypropylene/ethylene vinyl acetate blends - (:unkn) unknown (WILEY, 2005)
The effect of calcium carbonate (CaCO3) on the mechanical properties (with heat treatment) and thermal properties Of polypropylene and isotactic polypropylene (iPP)/ethylene vinyl acetate (EVA) blends was investigated. CaCO3, in five different concentrations (3, 6, 9, 121, and 15 wt %), was added to i-PP/EVA (88/12) to produce ternary composites. The mechanical properties, including the yield p V, and tensile strengths, elastic modulus, Izod impact strength for notch radii of 0.25 and 1 mm, and hardness with and without an annealing heat treatment, and the thermal properties, such as the melting point and melt-flow index, of the composites were investigated. The annealing heat treatment was carried out at 100 degrees C for three different holding times: 75, 100, and 150 h. On the basis of the results, attempts were made to establish a relationship between the CaCO3 content, the annealing holding time, and the mechanical and thermal properties to obtain the best results. The tensile test results showed that the heat treatment was not effective for the ultimate tensile strength, and the yield strength and tensile strength decreased gradually as the CaCO3 content increased. However, CaCO3 was effective for higher elastic modulus, impact strength, and hardness values. A consid-erable increase in the elastic modulus was found with a 3% CaCO3 concentration for a holding time of 100 h. The maximum impact strength for a notch radius of 1 mm was obtained with 3% CaCO3 with annealing for a holding time of 100 h, whereas a 9% CaCO3 concentration produced higher toughness values for a notch radius of 0.25 mm. The fracture surfaces also supported the results from the Izod impact tests. Similarly, hardness values increased with the annealing heat treatment and increasing CaCO3 content. However, different holding times showed similar effects on the hardness values. The increased CaCO3 content caused the melting point to increase 5 degrees C, whereas the melt-flow index showed a sharp decrease as the CaCO3 content increased to 3%. Taking into consideration the mechanical and thermal properties and the annealing holding time, we recommend a CaCO3 concentration of 3% with an annealing heat treatment for 100 h for optimum properties of such ternary composites. (c) 2005 Wiley Periodicals, Inc.
Keywords: compounding; injection molding; mechanical properties; poly(propylene) (PP); structure